The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4085/1062-6050-51.12.01
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Intermittent Postconcussion Symptoms After a Period of Symptom-Limited Physical and Cognitive Rest

Abstract: Reference: Schneider KJ, Iverson GL, Emery CA, McCrory P, Herring SA, Meeuwisse WH. The effects of rest and treatment following sport-related concussion: a systematic review of the literature. Br J Sports Med. 2013;47(5):304-307.Clinical Question: After concussion and a period of symptom-limited physical and cognitive rest, do athletes who experience intermittent symptoms return to asymptomatic condition more quickly with physical activity than with prolonged physical rest?Data Sources: One investigator perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…It is widely known that a constant level of physical exercise is one of the key components for overall health and to postpone aging-related disorders (1)(2)(3)(4)(5), in somatic and cognitive terms (6)(7)(8)(9)(10). Surprisingly, several recent studies have shown that aerobic exercise has beneficial consequences not only on bodily but also on cognitive functions (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that a constant level of physical exercise is one of the key components for overall health and to postpone aging-related disorders (1)(2)(3)(4)(5), in somatic and cognitive terms (6)(7)(8)(9)(10). Surprisingly, several recent studies have shown that aerobic exercise has beneficial consequences not only on bodily but also on cognitive functions (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Upon identification of neural regions of interest showing deficits in NVC, EPIC treatment integrates three fundamental neurocognitive rehabilitation components: Prepare, activate and rest. Therapeutic activities used in each of these three phases are the result of research, clinical experience, screening and empirical testing [88][89][90][91][92][93]. The preparatory stage includes aerobic exercise and neuromuscular therapy, titrated to patients exercise tolerance and lasts 50 min.…”
Section: Enhanced Performance In Cognition (Epic) Treatmentmentioning
confidence: 99%
“…Active rehabilitation is currently being assessed in larger clinical studies to determine if actively engaging studentathletes in specific tasks related to their symptoms helps them recover quicker. [5][6][7] What we are suggesting is a similar scaffolded model to follow for targeting cognitive symptoms monitored by an AT or school nurse. One possibility is that can we speed up recovery by providing active management using more targeted support and structured strategies instead of using a passive management model where we reintroduce and remove as needed up to return-to-learn or referred out.…”
Section: Active Management Of Return-to-learnmentioning
confidence: 99%
“…SLPs have the skills and expertise to help provide strategies to address the symptoms of concussions that affect cognitive processing, attention, and focus. Active rehabilitation is being considered to be worthwhile by leaders in the field, [5][6][7] and SLPs may be a logical way to help scaffold active cognitive recovery following a concussive injury. 5 Typical recovery time for concussions is 7 to 10 days with evidence that adolescents may take longer.…”
mentioning
confidence: 99%
See 1 more Smart Citation